USING INTERACTIVE LEARNING METHODS IN THE PROCESS OF PROFESSIONAL TRAINING OF FUTURE TEACHERS FOREIGN LANGUAGES (Pedagogy of Higher and Secondary Education, 2008)
In article to be considered effectiveness of using interactive methods of teaching in institution of higher educational in the process of preparing future teachers of foreign languages.